Cartography of littoral rocky-shore communities to assess the ecological status of water bodies through the application of CARLIT method in Algeria (South-Western Mediterranean Sea). (August 2020) - Bahbah, Lamia; Bensari, Bilel; Chabane, Khadidja; Torras, Xavier; Ballesteros, Enric; Seridi, Halima
Abstract: The cartography of shallow water macroalgal assemblages allows the assessment of water quality in coastal water bodies through the application of CARLIT. In this study, we have applied CARLIT to assess the ecological status of Algerian coastal water bodies for the first time. The surveyed zone is still in a good ecological status since 52% have a good to a high ecological Status. CARLIT index is well correlated with anthropogenic pressures and has proved suitable for the evaluation of the ecological status of coastal waters. Comparison between EQR values and EEI-c shows a similar pattern of change. CARLIT method allowed the collection of accurate information on the distribution and abundance of shallow-water communities. We also provide a cartographic baseline of the coastal assemblages useful for further evaluations on their geographic extension and for the implementation of a monitoring project on water quality in Algerian coast. Highlights: Application of CARLIT method and assessment of the water quality of Algerian coast First cartography of shallow macroalgal assemblages along the Algerian coastline Using macrophytes assemblages to assess an ecological status of coastal water Understanding of the composition structure and functioning of the coastal ecosystem Comparison of CARLIT index with other ecological indexes